Does more free childcare help parents work more? - Mike Brewer; Sarah Cattan; Claire Crawford; Birgitta Rabe (Institute for Fiscal Studies (IFS), 2020)
Many governments are considering expanding childcare subsidies to increase the labour force participation of parents (especially mothers) with young children. In this paper, we study the potential impact of such a policy by comparing the effects of offering free part-time childcare and of expanding this offer to the whole school day in the context of England. We use two different strategies exploiting free childcare eligibility rules based on date of birth. Both strategies suggest that free part-time childcare only marginally affects the labour force participation of mothers whose youngest child is eligible, but expanding from part-time to full-time free childcare leads to significant increases in labour force partici-pation and employment of these mothers. These effects emerge immediately and grow over the months following entitlement. We find no evidence that parents adjust their labour supply in anticipation of their children's entitlement to free childcare.
Keywords: I21; J22; 330; Labour supply; childcare; school entry